Workshop Production of Liquid Soap Made from Arabica Coffee and Yogurt in Cibiru, Bandung to Develop Hygiene Lifestyle - Rum, Ira Adiyati; Supriadi, Dadih; Kurnia, Dewi; Mardhiani, Yanni Dhiani; Kosasih, Kosasih (Inaba of Community Services Journal, 2024)
Few communities in Cibiru have a problem, namely that they have not implement a clean and healthy lifestyle, namely the lack of the habit of washing hands with soap before eating, especially for children, resulting in moderate diarrhea in the community area, as well as a lack of post-harvest diversification of coffee and milk. The solution   provided is to educate the community by presentation about the importance of washing hands with soap before eating. This event also holds training in making liquid hand washing soap, so that people are skilled at making the product, and can even sell the product. There are three specific goals and targets to be achieved, namely the community gaining knowledge on how to make hand washing soap, the community get used to a clean and healthy lifestyle and increasing community income by selling the liquid soap. The methods that are used are presentation of material using in focus and Microsoft PPT, training in making hand-washing soap products (hands-on) and monitoring post-training product marketing. The method used to make this hand washing soap is the fermentation method for making yogurt, the maceration method for making Arabica coffee extract. From the results of the questionnaire evaluation, there was an increase in participants' insight after being given the training, namely from an average score of 68 to 90, so there is quantitative data on the results of this training